Pengaruh Motivasi, Lingkungan dan Kepuasan Kerja terhadap Turnover Intention pada Karyawan PT. Astra Motor Rembang 1 Kecamatan Rembang Kabupaten Rembang - Karimah, Eny Himatul; Nurhidayati, Anik (Innovative: Journal Of Social Science Research, 2025)
This study aims to prove the influence of motivation, environment, and job satisfaction on turnover intention of employees of PT Astra Motor Rembang 1, Rembang District, Rembang Regency. This study has a population of employees of PT Astra Motor Rembang 1, Rembang Regency. The sampling technique uses saturated probability sampling. This study involved 42 respondents. Multiple linear regression was used to analyze the data. The results showed that factors such as motivation, work environment, and negative job satisfaction were not significant to employees' desire to leave the company PT Astra Motor Rembang 1, Rembang Regency. The Adjusted R Square value of this study is 0.508, or 50.8 percent, which indicates that the variability of the dependent variable, exchange intention, can be explained by the independent variables, namely motivation, work environment, and job satisfaction, by 50.8 percent. Other independent variables, which are not explained in this study, contribute 49.2 percent.